2007
DOI: 10.1159/000112413
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Oxidative Stress but Not in Antioxidant Capacity with Advancing Stages of Chronic Kidney Disease

Abstract: Background/Aims: Increased oxidative stress in chronic kidney disease (CKD) was suggested to be both a cause and an effect of renal injury. However, the evolution of oxidant stress from early stages of renal function decline is not fully clear. This study aimed to determine the oxidant-antioxidant balance across the whole range of renal function. Methods: A total of 116 patients with CKD (85 predialysis patients divided into groups according to CKD stage, and 31 patients with end-stage renal disease (ESRD) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 75 publications
3
92
1
3
Order By: Relevance
“…Aslan et al found lower serum levels of antioxidants in type 2 diabetic patients with microalbuminuria, but provided no data on glyco-oxidation [38]. Other authors found that serum levels of antioxidants were much the same and tended to remain stable in various stages of non-metabolic kidney disease (changing only in patients with end-stage renal disease) despite a progressive increase in oxidative stress [39]. Our data from the PCA analysis suggest that microalbuminuria in type 2 diabetic patients might be promoted by an insufficient counter-regulation of the antioxidant system in the event of increased glycooxidation/glycation.…”
Section: Discussionmentioning
confidence: 98%
“…Aslan et al found lower serum levels of antioxidants in type 2 diabetic patients with microalbuminuria, but provided no data on glyco-oxidation [38]. Other authors found that serum levels of antioxidants were much the same and tended to remain stable in various stages of non-metabolic kidney disease (changing only in patients with end-stage renal disease) despite a progressive increase in oxidative stress [39]. Our data from the PCA analysis suggest that microalbuminuria in type 2 diabetic patients might be promoted by an insufficient counter-regulation of the antioxidant system in the event of increased glycooxidation/glycation.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5] Indeed, oxidative stress and impaired antioxidant capacity intensify with progression of CKD, 6,7 and production of reactive oxygen species and oxidative stress result in activation of the transcription factor nuclear factor kB (NFkB). NFkB regulates expression of proinflammatory cytokines and chemokines, and its pathologic activation is a hallmark of many inflammatory disorders, including CKD.…”
mentioning
confidence: 99%
“…They proposed that vitamin E supplementations could increase the levels of vitamin E as well as vitamin C. 22 Ioannis Karamouzis et al (2008) and Mehri Kadkhodaee et al (2008) observed lower values of plasma vitamin E in CRF patients as compared to controls. 23,24 Francesco Galli et al also observed decreased vitamin E levels in patients of chronic renal failure patients on hemodialysis. 25 In contrast, some studies have indicated normal or higher values of vitamin E in the chronic renal failure patients.…”
Section: Discussionmentioning
confidence: 95%